2016
DOI: 10.1016/j.adolescence.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parenting quality on adolescents' personality resemblance to their parents. The TRAILS study

Abstract: This study considers the development of resemblance between 741 adolescents and their biological parents, across six NEO‐PI‐R personality traits known to be important in psychological problems: anger‐hostility, impulsiveness, vulnerability, assertiveness, excitement‐seeking, and self‐discipline. We modelled the association between perceived parental warmth and rejection at age eleven and personality resemblance to parents at about age sixteen. Parenting experienced during early adolescence was related to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 138 publications
3
9
0
1
Order By: Relevance
“…Robins, Caspi, & Moffitt, ; Selfhout et al, ), little is known regarding personality similarity between parents and offspring. Only two previous studies examined parent–offspring personality similarity (Langenhof, Komdeur, & Oldehinkel, ; Van Tuijl et al, ), suggesting that personality similarity might play an important role in offspring's development. However, it is not known whether the level of personality traits affects the impact of personality similarity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Robins, Caspi, & Moffitt, ; Selfhout et al, ), little is known regarding personality similarity between parents and offspring. Only two previous studies examined parent–offspring personality similarity (Langenhof, Komdeur, & Oldehinkel, ; Van Tuijl et al, ), suggesting that personality similarity might play an important role in offspring's development. However, it is not known whether the level of personality traits affects the impact of personality similarity.…”
mentioning
confidence: 99%
“…The two studies investigating parent–offspring similarity in personality indicated that, when similarity mattered, it was associated with fewer externalizing problems (Langenhof et al, ; Van Tuijl et al, ). From an evolutionary perspective, such similarity might be beneficial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Parenting styles (IV) based on responsiveness and demandingness (authoritarian, authoritative and permissive) and on the other hand, dependent variable (DV) Big five personality traits (extraversion, agreeableness, conscientiousness, neuroticism and openness) were analyzed through the Pearson correlation for the identification of correlation, direction and consistency of the relationship between IV and DV results revealed that there was a significant correlation (p<0.01**) between parenting styles and personality traits. Langenhof, Komdeur and Oldehinkel (2016) stated that there was a significant relationship between parenting styles and personality resemblance (p<0.01 or 0.02) a parent's personality was a correlated with parent-child distinctions (adolescents were different from their parents) the researcher had applied the Pearson correlation on parental personality and children differences with respect to the corresponding personality of parents which was based on mildness &rejection of parents towards the child. As present results, showed there was a significant correlation between parenting style and personality traits at P<0.01**.…”
Section: Discussionmentioning
confidence: 99%
“…В долгосрочных отношениях между родителями и детьми постоянно оказывается прямое и косвенное влияние на собственных родителей. В течение обучения детей отцы становятся более уверенными и самодисциплинированными [19].…”
Section: вклад отцов в развитие детейunclassified